Acromegaly Caused by Ectopic Growth Hormone Releasing Hormone Secretion: A Review - Zendran, Iga; Gut, Gabriela; Kałużny, Marcin; Zawadzka, Katarzyna; Bolanowski, Marek (Frontiers in Endocrinology, 2022)
Introduction: Ectopic acromegaly is a rare condition caused most frequently by growth hormone releasing hormone (GHRH) secretion from neuroendocrine tumors. The diagnosis is often difficult to establish as its main symptoms do not differ from those of acromegaly of pituitary origin. Objectives: To determine most common clinical features and diagnostic challenges in ectopic acromegaly. Patients and methods: A search for ectopic acromegaly cases available in literature was performed using PubMed, Cochrane and MEDline database. 127 cases of ectopic acromegaly described after GHRH isolation in 1982 are comprehensively reviewed in this article, along with a summary of current state of knowledge on its clinical features, diagnostic methods and treatment modalities. The most important data were compiled and compared in the tables. Results: Neuroendocrine tumor was confirmed in 119 out of 121 patients with histopathological evaluation, mostly of lung and pancreatic origin. Clinical manifestation comprise symptoms associated with pituitary hyperplasia, such as headache or visual field disturbances as well as typical signs of acromegaly. Other endocrinopathies may also be present depending on the tumor type. Definitive diagnosis of ectopic acromegaly requires confirmation of GHRH secretion from a tumor using either histopathological methods or GHRH plasma concentration assessment. Hormonal evaluation was available for 84 patients (66%) and histopathological confirmation for 99 cases (78%) . Complete tumor resection was the main treatment method for most patients, as a treatment of choice due to its highest effectiveness. When not feasible, somatostatin receptor ligands (SRL) therapy is the preferred treatment option. Prognosis is relatively favorable for neuroendocrine GHRH-secreting tumors with high survival rate. Conclusion: Although ectopic acromegaly remains a rare disease, one should be aware of it as a possible differential diagnosis in patients presenting with additional symptoms or those not responding to classic treatment of acromegaly.